Cuidado parental de Selenidera Maculirostris, Pteroglossus Castanotis e Ramphastos Toco (Piciformes - Ramphastidae), no interior de ninhos - Cziulik, Marcia (2010)
Orientador : Prof. Dr. Emygdio L.A. Monteiro Filho